PRESENCE OF STAPHYLOCOCCUS AUREUS ENTEROTOXIN GENES IN MILK AND DAIRY PRODUCTS - A REVIEW - Sindjic, Milijana (Food and Feed Research, 2025)
Staphylococcus aureus is a highly adaptable microorganism that is commonly found in a variety of settings, including the skin and mucous membranes of humans and animals, as well as in the air, soil, and water. It is widely known for possessing a variety of virulence factors that enable it to cause and spread diseases. The presence of the genes for TSST-1 and enterotoxin A in milk and milk products will receive the most emphasis in this review. S. aureus isolated from milk can carry individual or combinations of genes coding for classical enterotoxins. The expression of many virulence-related genes S. aureus is regulated by the agr (accessory gene regulator) system, a two-component signaling system that down-regulates surface proteins and up-regulates secretory proteins, including various enterotoxins such as SEB, SEC, SED, and TSST-1. Staphylococcal food poisoning (SFP) is commonly linked to the growth of staphylococci in protein-rich foods, for example, meat, milk, and dairy products. The growth of S. aureus and the production of enterotoxins are heavily influenced by the characteristics of the food, including salt content, pH, nutrient availability, oxygen levels, and temperature. In the dairy industry, strict control methods and ongoing monitoring are necessary to guarantee food safety. Long-term storage of milk above 8°C greatly raises the danger of S. aureus growth and the possibility of enterotoxin development.
Keywords: enterotoxin A; toxic shock syndrome toxin-1; food safety; dairy